The specification of geometric edges by a plant Rab gtpase is an essential cell-patterning principle during organogenesis in Arabidopsis - Kirchhelle, C; Chow, C; Foucart, C; Neto, H; Stierhof, Y; Kalde, M; Walton, C; Fricker, M; Smith, R; Jérusalem, A; Irani, N; Moore, I (Cell Press, 2016)
Plant organogenesis requires control over division planes and anisotropic cell wall growth, which each require spatial patterning of cells. Polyhedral plant cells can display complex patterning in which individual faces are established as biochemically distinct domains by endomembrane trafficking. We now show that, during organogenesis, the Arabidopsis endomembrane system specifies an important additional cellular spatial domain: the geometric edges. Previously unidentified membrane vesicles lying immediately beneath the plasma membrane at cell edges were revealed through localization of RAB-A5c, a plant GTPase of the Rab family of membrane-trafficking regulators. Specific inhibition of RAB-A5c activity grossly perturbed cell geometry in developing lateral organs by interfering independently with growth anisotropy and cytokinesis without disrupting default membrane trafficking. The initial loss of normal cell geometry can be explained by a failure to maintain wall stiffness specifically at geometric edges. RAB-A5c thus meets a requirement to specify this cellular spatial domain during organogenesis.